Bidding-based process planning and scheduling in a multi-agent system - Gu, P.; Balasubramanian, S.; Norrie, D.H. (Computers & industrial engineering, 1997)
Effective and efficient implementation of intelligent and/or agile manufacturing systems requires an enterprise level integration. The first step in this direction is to integrate design, process planning and and scheduling. This paper describes a bidding-based approach to the integration of computer-aided design, process planning and real time scheduling. The product is represented in a STEP model with detailed design and administrative information including design specifications, batch size, and due dates. Upon arrival at the manufacturing facility, the product is registered in the shop floor manager which is essentially a coordinating agent. The shop floor manager broadcasts the product's requirements to the machines. The shop contains autonomous machines that have knowledge about their functionality, capabilities, tooling and schedules. Each machine has its own process planner and responds to the product's request in a way that is consistent with its capabilities and capacities. When more than one machine offers certain process(es) for the same requirements, they enter into negotiation. Based on processing time, due date and cost, one of the machines wins the contract. The successful machine updates its schedule and advises the product to request raw material for processing. The concept was implemented using a multi-agent system in an object-oriented programming language. The task decomposition and planning are achieved through contract nets. Examples are included to illustrate the approach.